The eff ect of simulated tennis tournament play on selected performance measure - Angeleau Scott; Michael Wilson; Dimitrije Cabarkapa; Andrew Fry; Mary Fry (Journal of Applied Sports Sciences)
Tennis is a sport that requires a mix of both anaerobic and aerobic energy systems. Many studies have quantifi ed performance metrics of tennis populations related to sprinting, jumping, aerobic endurance, and other metrics, but no studies have quantifi ed performance and endocrine measures during live gameplay. The purpose of this study was to analyze the eff ects of multiple tennis matches on selected measures of performance and physiological responses in male adult tennis players. Eleven amateur male adult tennis players participated in fi ve 70-minute (3 single and 2 doubles) matches with ~30 minutes of rest between matches. Testing included: agility, 20-yard sprint times, service speed, dominant hand grip strength, vertical jump height (VJH), peak power derived from jump height (PPj), mean power derived from jump height (MPj), and performance on a 10-sec modifi ed Wingate test which resulted in the determination of peak power (PP) and mean power (MP). Serum concentrations of cortisol, testosterone, IgA, IgM, and IgG were also collected. Results of repeated measured ANOVA (p < .05) indicated that (mean ± SE) agility (13.17 ± 0.68-10.41 ± 0.24 sec), VJH (45.95 ± 2.59-44.91 ± 2.18 cm), PPj (7608.47 ± 43.90-7531.50 ± 119.79 Watts), MPj (1460.84 ± 54.42-1430.73 ± 48.75 Watts), PP (949.55 ± 30.85-783.32 ± 27.99 Watts) and MP (823.61 ± 27.77-783.32 ± 30.36 Watts) signifi cantly decreased by the end of the simulated tournament. Results suggest that there is a signifi cant demand for short-term aerobic power and capacity after playing multiple tennis matches. Therefore, training programs need to be adopted by amateur male adult tennis players to meet these demands.